GroupTracker: Video tracking system for multiple animals under severe occlusion. (August 2015) - Fukunaga, Tsukasa; Kubota, Shoko; Oda, Shoji; Iwasaki, Wataru
Abstract : Graphical abstract: Abstract : Highlights: We developed "GroupTracker", a new multiple animal tracking system. This system accurately tracks individuals even under severe occlusion. We devised an EM scheme with constraints on the eigenvalues of the covariance matrix. We aim at revealing behavioral patterns behind animal interactions using our software. Abstract: Quantitative analysis of behaviors shown by interacting multiple animals can provide a key for revealing high-order functions of their nervous systems. To resolve these complex behaviors, a video tracking system that preserves individual identity even under severe overlap in positions, i.e., occlusion, is needed. We developed GroupTracker, a multiple animal tracking system that accurately tracks individuals even under severe occlusion. As maximum likelihood estimation of Gaussian mixture model whose components can severely overlap is theoretically an ill-posed problem, we devised an expectation–maximization scheme with additional constraints on the eigenvalues of the covariance matrix of the mixture components. Our system was shown to accurately track multiple medaka ( Oryzias latipes ) which freely swim around in three dimensions and frequently overlap each other. As an accurate multiple animal tracking system, GroupTracker will contribute to revealing unexplored structures and patterns behind animal interactions. The Java source code of GroupTracker is available athttps://sites.google.com/site/fukunagatsu/software/group-tracker .